Discovery of novel substituted benzo-anellated 4-benzylamino pyrrolopyrimidines as dual EGFR and VEGFR2 inhibitors. Issue 12 (15th June 2017) - Fischer, Tim; Krüger, Thomas; Najjar, Abdulkarim; Totzke, Frank; Schächtele, Christoph; Sippl, Wolfgang; Ritter, Christoph; Hilgeroth, Andreas
Graphical abstract: Abstract: The quinazoline scaffold is the main part of many marketed EGFR inhibitors. Resistance developments against those inhibitors enforced the search for novel structural lead compounds. We developed novel benzo-anellated 4-benzylamine pyrrolopyrimidines with varied substitution patterns at both the molecular scaffold and the attached residue in the 4-position. The structure-dependent affinities towards EGFR are discussed and first nanomolar derivatives have been identified. Docking studies were carried out for EGFR in order to explore the potential binding mode of the novel inhibitors. As the receptor tyrosine kinase VEGFR2 recently gained an increasing interest as an upregulated signaling kinase in many solid tumors and in tumor metastasis we determined the affinity of our compounds to inhibit VEGFR2. So we identified novel dually acting EGFR and VEGFR2 inhibitors for which first anticancer screening data are reported. Those data indicate a stronger antiproliferative effect of a VEGFR2 inhibition compared to the EGFR inhibition.